(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Self-esteem is an essential component of self-awareness. It occupies a key place in the structure of pre-teen individuals because it is related to mental health and the definition of life goals. Pre-teens with self-esteem feel liked, accepted, and confident. They’re proud of what they can do and think good things about themselves. Pre-tenders with low self-esteem criticize themselves and doubt they can do things well. They feel they’re not as good as other kids and think of the times they fail rather than when they succeed. Self-esteem helps kids do better at school, at home, and with friends. Pre-teens with low self-esteem feel unsure of themselves. If they think others won’t accept them, they may not join in. They may let others treat them poorly and have a hard time standing up for themselves. They may give up easily or not try at all.Pre-teen students with low self-esteem find it hard to cope when they make a mistake, lose, or fail. So they may not do as well as they could. In the short term, these children often experience loneliness, low self-esteem, and social anxiety. Long-term consequences include poor academic performance, school dropout, juvenile delinquency, criminal behavior, and mental health problems, particularly externalizing ones, in adolescence and adulthood. School is a great place for children to learn to socialize, rationalize their feelings, and boost their academic prowess, but school cannot teach children everything they need to know, especially when it comes to social and emotional quotient. The Adversity Quotient (AQ) is an innate ability that enables people to turn their adverse situations into life-changing advantages. Determining students and their influence on other factors that affect achievement is likely to provide greater understanding and better prediction of academic achievement. Much research has been carried out on this concept without focussing on its combined impacts with student-teacher psychological factors on academic achievement among pre-teen students.